Comparative evaluation of intubation difficulty score using C-Mac video-laryngoscope and macintosh laryngoscope in obese patients undergoing general anaesthesia - Malik, Neha; Shabeen, Ghazala (International Journal of Research in Medical Sciences, 2024)
Background: Obesity, a global epidemic, predicted to have difficult airways which can be evaluated preoperatively with advancement of technologies for airway management. The present prospective study was done to evaluate and compare the intubation difficulty score (IDS) in videolaryngoscope with standard Macintosh laryngoscope. Methods: Our study included 50 obese patients divided into two groups: Group OC (intubation done with C-Mac videolaryngoscope) and Group OM (Macintosh laryngoscope). The patients were evaluated for macroglossia, upper lip bite test, modified Mallampati grade, inter incisor gap and Wilson score in preoperative period. Intraoperatively IDS, time taken for intubation and complications were studied. Results: IDS has sensitivity and specificity of 82.3% and 66.67% respectively. 12 patients in OM group and 3 in OC group had very difficult IDS (48% vs. 12%; p <0.05). Mean time taken for intubation was more in OM group (26.08 +/- 9.8 secs) as compared to OC group (15.96 +/- 7.2 secs). Inter incisor gap grade 2 have 8.3% of patients in easy IDS, 30.4% moderately difficult and 53.3% in very difficult IDS (p<0.05). Very difficult IDS group had total Wilson score of 5.60 as compared to 4.52 in moderately difficult group and 3.17 in easy IDS group. Conclusions: This study reveals that as compared to standard Macintosh laryngoscope, C-Mac videolaryngoscope is better for intubation in obese patients in terms of IDS. Time taken for intubation and complications are less with videolaryngoscope. Inter incisor gap and Wilson score measured pre operatively are significant predictor of difficult airway in relation with IDS.